The Effect of Learning Strategy and Preliminary Ability on The Results of Learning Kearsipan Course in the Polytechnic of LP3i Jakarta - Badriyah Badriyah; Hartati Muchtar; Moch. Sukardjo (International Journal of Education, Information Technology, and Others, 2020)
This research was conducted at the LP3I Jakarta Polytechnic, Business Administration Study Program for the even semester of the 2019/2020 academic year in November 2019 to March 2020 with treatment given for 8 (eight) meetings including the initial test and final test using the experimental method, while the research design was design. treatment by level 2 x 2. The purpose of this study was to determine the differences in learning outcomes of archiving subjects in office administration students, between students who studied PBL (Problem Based Learning) learning strategies and students who studied withlearning strategies CTL (Contextual Teaching Learning) and The interaction between learning strategies and early office administration skills on learning outcomes of archiving subjects. The influence oflearning strategies PBL (Problem Based Learning) is higher for students who have a low level of initial ability than thelearning strategy CTL (Contextual Teaching Learning) on archiving learning outcomes. Students with low initial abilities usinglearning strategies PBL (Problem Based Learning) will be better at solving problems with group friends. So that thelearning strategy PBL (Problem Based Learning) has a greater influence on students who have a low initial ability level compared to using thelearning strategy CTL (Contextual Teaching Learning). To improve archival learning outcomes for students at the LP3I Jakarta Polytechnic, office administration majors that have high initial abilities uselearning strategies. PBL (Problem Based Learning) learning outcomes are higher, as well as for students who have low initial abilities, their learning outcomes can be improved by followinglearning strategies. PBL (Problem Based Learning), in general, to improve the learning outcomes of LP3I Jakarta Polytechnic students, office administration majors can be done using thelearning strategy. PBL (Problem Based Learning).